Amphimonhystrella tropica sp. n. and Oncholaimus mekongis sp. n. (Nematoda) from the Mekong River, Vietnam - Gagarin V.G. & Gusakov, V.A. (Inland Water Biology, 2023)
Illustrated descriptions of two new free-living nematode species, Amphimonhystrella tropica sp. n.and Oncholaimus mekongis sp. n., found in the Mekong River delta (Vietnam) are given. A. tropica is similar to A. major Gagarin, Nguyen Dinh Tu, 2021 and A. paramonovi (Phan Ke Long, Nguyen Dinh Tu, Gagarin, 2020) in body size. It differs from first species in pharyngostoma shape, thicker body, longer tail and spicules, and by the absence of posterior uterus sac. It differs from second species in its thicker body, longer spicules, and different gubernaculum structure. Daptonema paramonovi Phan Ke Long, Nguyen Dinh Tu, Gagarin, 2020 is transferred to the genus Amphimonhystrella Timm, 1961: A. paramonovi (Phan Ke Long, Nguyen Dinh Tu, Gagarin, 2020) comb. nov. Dichotomy and pictorial keys for the identification of males of valid species of the genus Amphimonhystrella are given. Oncholaimus mekongis sp. n. is similar to O. balli (Kreis, 1934) and O. menzeli Schneider, 1973 in body size and spicule length. It differs from both species by the presence of big spiny seta in the precloaca area, the position of ventral papillae on tail in males, a thicker body, shorter outer labial setae, and a longer and more slender tail in males.